2015
DOI: 10.3111/13696998.2015.1025793
|View full text |Cite
|
Sign up to set email alerts
|

Utilities for asthma and COPD according to category of severity: a comprehensive literature review

Abstract: Utilities have been summarized according to severity category of asthma and COPD. These values should be useful for researchers undertaking economic analyses of these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 103 publications
0
15
0
1
Order By: Relevance
“…A meta-analysis study acknowledged a considerable amount of variation across studies. However, there was consensus on the finding that the greater the severity, the greater the degree of deterioration of quality of life [10,11,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis study acknowledged a considerable amount of variation across studies. However, there was consensus on the finding that the greater the severity, the greater the degree of deterioration of quality of life [10,11,47].…”
Section: Discussionmentioning
confidence: 99%
“…Pickard et al [10] and Einarson et al [11] reported that the utility measure reflects the clinical severity of COPD well, as evidenced by lower utility scores when disease severity is higher. However, many other studies have reported that the discriminatory ability of a multi-attribute utility (MAU) measure, such as the five-dimensional EuroQol (EQ-5D) utility index, is limited with respect to measuring the quality of life of patients with COPD [4,[10][11][12][13][14]. Therefore, there is an increasing tendency to use condition-specific measures (CSMs), which are more sensitive to the detection of small treatment effects.…”
Section: Introductionmentioning
confidence: 99%
“…Einarson et al reviewed 44 original articles that reported utilities related to COPD [ 41 ]. Irrespective of disease classification and utility instrument, methods or tariffs used, mean utilities were 0.83, 0.77, 0.71, and 0.61 for GOLD grades 1–4 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Es posible que la pérdida de peso en pacientes con EPOC gradados en GOLD C y D sea en sí mismo un indicador de deterioro funcional y no la causa de éste, es decir, no es la falta de peso por pérdida de masa muscular o grasa corporal responsable del deterioro de la función pulmonar, el funcionamiento global y la mortalidad del paciente con EPOC (6,19,28) . De igual manera, considerar la naturaleza arbitraria de la clasificación GOLD que ha mostrado problemas por no seguir una secuencia lineal de menor a mayor frecuencia de exacerbaciones, A<B<C<D y las variaciones importantes que se dan en la clasificación según la escala usada para cuantificar los síntomas (29,30) .…”
Section: Discussionunclassified